HISTÓRIA, LINGUAGEM E ALEGORIA EM WALTER BENJAMIN - COELHO FILHO, William (2022)
This dissertation aims to present Walter Benjamin's conception of language and its philosophical and historiographical presentation (Darstellung). The research proposal is to discuss this historical-philosophical reflection as an experience of language (Erfahrung der Sprache ) and as a political task (Aufgabe) that involves the exercise (Übung) of rehabilitation of what was silenced, forgotten and neglected by positivist historicism. The dissertation addresses the idea built by the German baroque theater of the 17th century as an acute expression of the Hippocratic facies of history and nature, marked by decrepitude and ruin. It is also discussed here Benjamin's reception of Charles Baudelaire's nineteenth-century allegorical poetry and its emancipatory possibilities of culture in the face of ephemeral and transitory modern life.The critique of the ideology of progress together with the construction of a philosophical and poetic language are able to think about the historical transformations currently underway, as they are fundamental to keep alive the main ideas of the Berliner philosopher about language, about modernity, literature and history.